2005
DOI: 10.1016/j.amjhyper.2005.04.017
|View full text |Cite
|
Sign up to set email alerts
|

Felodipine–Metoprolol Combination Tablet: Maintained Health-Related Quality of Life in the Presence of Substantial Blood Pressure Reduction

Abstract: The HRQL is maintained in the presence of substantial BP reduction during antihypertensive treatment with F+M fixed combination tablets.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
21
0

Year Published

2006
2006
2018
2018

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 18 publications
(22 citation statements)
references
References 22 publications
0
21
0
Order By: Relevance
“…recent data suggest that patients with established hypertension receiving pharmacotherapy may feel better as blood pressure is lowered because of symptom improvement, regardless of the type of medication given. 2,15 angiotensin-converting enzyme inhibitors and angiotensin ii receptor antagonists may offer some advantage with regard to effects on cognitive function and sexual activity 16 ; one study has also suggested that a calcium channel blocker-based treatment regimen lowered the incidence of dementia.…”
Section: Boi Analysismentioning
confidence: 99%
“…recent data suggest that patients with established hypertension receiving pharmacotherapy may feel better as blood pressure is lowered because of symptom improvement, regardless of the type of medication given. 2,15 angiotensin-converting enzyme inhibitors and angiotensin ii receptor antagonists may offer some advantage with regard to effects on cognitive function and sexual activity 16 ; one study has also suggested that a calcium channel blocker-based treatment regimen lowered the incidence of dementia.…”
Section: Boi Analysismentioning
confidence: 99%
“…Such a favorable finding agrees with a previous report. 24 There were no significant side-effects in both treatment groups. However, BNP significantly increased in the betaxolol adding group after 6 months of treatment.…”
Section: Discussionmentioning
confidence: 94%
“…Significant differences in HRQL scores between treatments were observed in our study. Recent data [12,13] suggest that patients with established hypertension receiving pharmacotherapy may feel better as blood pressure is lowered because of symptoms improvement, regardless of the type of the medication given. The current study's results are consistent with previous studies evaluating the effect of antihypertensive medications on HRQL.…”
Section: Discussionmentioning
confidence: 99%